Abraham as an iconoclast: understanding the destruction of "images" throught Qur'anic exegesis - Mirza, Younus Y. (Islam and Christian-Muslim relations, 2005)
The question of Islam and its aversion to images has caused modern scholars to search for a theological basis in Islam's traditional sources. Much work has been done on the various hadiths that indicate that graven images are forbidden and particular verses in the Qur'an that allude to an aversion to them. However, little work has been done to understand this issue through the qur'anic parables and exegesis. This paper explores the issue of Islam and image through qur'anic exegesis, in particular, the story of Abraham as a youth breaking the idols in his polytheistic town. By tracing the commentary of some of the major exegetes of the Qur'an, such as al-&art6;abarī, al-Rāzī, Ibn Kathīr and Sayyid Qu&art5;b, this article considers how Islam has viewed images and how that view has either fluctuated or remained constant over time.